Analisis Perubahan Iklan pada Media Televisi dalam Acara Liputan6 ke Media Digital Liputan6.com - Deony Dewanggi Mulyono (Jurnal Riset Komunikasi (JURKOM), 2021)
Unbound within space, time and not require lots of money to make digital media more popular in public. Other than that, the wide market reach also makes company owners consider to spend their advertising on online media. As well as advertising in Liputan6.com, that can be said, have increased, because of these circumstances. The activities of the people who use gadget more frequently for looking up some informations has become kind of support for the increasing of advertising spending in digital media. The aim of these research is to see how the advertising transition in Liputan6 television program into Liputan6.com digital media. This research uses a qualitative descriptive as the method, with literature study technique. The analysis, shows that digital advertisements gaining more attention, especially in Liputan6.com media. It happens because people consume the internet often, the advertising concept of Liputan6.com is more attractive, and the difference cost of advertisements between Liputan6 program and Liputan6.com digital media.